Cities Think Underground – Underground Space (also) for People. (2017) - Besner, Jacques
Abstract: The ACUUS, the Associated research Centers for the Urban Underground Space, was established in Montreal in 1997 to promote partnership amongst all actors involved in the planning, design, construction, management and research on urban underground space. To explain how ACUUS has become an international organization over the years, and recognized by UN-Habitat, the evolution of global attention on underground space since the 19th century, with the gradual arrival of national and international organizations dedicated to the underground. Based on personal experience as a municipal planner, ways in which urban underground space should be planned and managed are described. The underground should be a place for people as much as for tunnels and public utilities. Montreal Underground City, one of the largest of its kind in the world, is used to demonstrate how, since 1962, underground use can evolve and the sub-surface can be "humanized". Some global trends are described, and challenges that need to be overcome in order to "populate" the underground, are also highlighted.